STUDY AND CORRECTION OF MICROELEMENT IMBALANCE IN PATIENTS WITH GIARDIASIS - Duysenova Gulzar Karlibaevna (TADQIQOTLAR, 2026)
Abstract Giardiasis is a widespread parasitic disease that often leads to chronic gastrointestinal disorders, malabsorption, and metabolic disturbances. One of the important but insufficiently studied consequences of giardiasis is the imbalance of essential microelements. The study included patients diagnosed with giardiasis based on parasitological and immunological tests. Serum levels of essential microelements were determined before and after treatment. Patients received standard antiparasitic therapy combined with microelement correction.